Uncharitable Film Review - Susan Appe; Bruna De Morais Holanda (Journal of Social Equity and Public Administration)
"Uncharitable" is a 2023 documentary directed by Stephen Gyllenhaal, based on Dan Pallotta's 2008 book of the same name, and incorporating Pallotta's Ted Talk delivered in March 2013. Dan Pallotta is a well-known figure in the nonprofit world and the movie itself will be familiar to those who have followed his work. The documentary emphasizes the need to reconsider the rules of the game that shape philanthropy and the nonprofit sector. We provide a review of the film given the important role the nonprofit sector plays in influencing and contributing to public administration and policy; and in the provision of public goods and services.